Effects of a 6-week plyometric training program on performances in pubescent swimmers - Potdevin, F. J.; Alberty, M. E.; Chevutschi, A.; Pelayo, P.; Sidney, M. C. (The Journal of Strength and Conditioning Research, 2011)
This study examined in pubescent swimmers the effects on front crawl performances of a 6-week plyometric training (PT) in addition to the habitual swimming program. Swimmers were assigned to a control group (n = 11, age: 14.1 ± 0.2 years; GCONT) and a combined swimming and plyometric group (n = 12, age: 14.3 ± 0.2 years; GSP), both groups swimming 5.5 h/wk during a 6-week preseason training block. In the GSP, PT consisted of long, lateral high and depth jumps before swimming training 2 times per week. Pre and posttests were performed by jump tests (squat jump [SJ], countermovement jump [CMJ]) and swim tests: a gliding task, 400- and 50-m front crawl with a diving start (V400 and V50, m/s), and 2 tests with a water start without push-off on the wall (25 m in front crawl and 25 m only with kicks). Results showed improvement only for GSP for jump tests (d= 4.67 ± 3.49 cm; d= 3.24 ± 3.17 cm; for CMJ and SJ, respectively; p < 0.05) and front crawl tests (d = 0.04 ± 0.04 m/s; Delta = 0,04 ± 0.05 m/s; for V50 and V400, respectively; p < 0.05). Significant correlations were found for GSP between improvements in SJ and V50 (R = 0.73, p < 0.05). Results suggested a positive effect of PT on specific swimming tasks such as dive or turn but not in kicking propulsion. Because of the practical setup of the PT and the relevancy of successful starts and turns in swimming performances, it is strongly suggested to incorporate PT in pubescent swimmers' training and control it by jump performances.